2022
DOI: 10.1097/qad.0000000000003394
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 subtype B spread through cross-border clusters in the Balkans: a molecular analysis in view of incidence trends

Abstract: Objectives:To analyze phylogenetic relations and assess the role of cross-border clusters in the spread of HIV-1 subtype B across the Balkans, given the general trends of new HIV diagnoses in seven Balkan countries.Design:Retrospective phylogenetic and trend analysis.Methods:In-depth phylogenetic, phylodynamic and phylogeographic analysis performed on 2415 HIV-1 subtype B sequences from 1999 to 2019 using maximal likelihood and Bayesian methods. The joinpoint regression analysis of new HIV diagnoses by country… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
(67 reference statements)
1
3
0
Order By: Relevance
“…In contrast, CRF01_AE was found mostly in PWIDs and rarely in MMSCs. The differences in the prevalence of these subtypes among MMSC and PWIDs are most likely a consequence of their initial introduction into these groups, followed by rapid dissemination among these populations, as described in our previous studies [20][21][22]55,56]. This result is supported by our finding of transmission clusters containing sequences from people with different transmission risk behaviors.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, CRF01_AE was found mostly in PWIDs and rarely in MMSCs. The differences in the prevalence of these subtypes among MMSC and PWIDs are most likely a consequence of their initial introduction into these groups, followed by rapid dissemination among these populations, as described in our previous studies [20][21][22]55,56]. This result is supported by our finding of transmission clusters containing sequences from people with different transmission risk behaviors.…”
Section: Discussionsupporting
confidence: 88%
“…Further, as phylogenetic research has demonstrated, viruses and thus pandemics spread from one country to another, with those countries that respond poorly acting as sources for new strains with mutations potentially affecting transmissibility, pathogenicity, or vaccine-induced protection, and potentially as sources of transmission to countries with more effective responses [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] and to countries linked by the movement of commodities and people. Diagnostic tools to understand how to reduce such spread and how to optimize international cooperation in response to it are needed.…”
Section: No Country Is An Island: One Country’s Failure Creates Probl...mentioning
confidence: 99%
“…21 Population movement was an independent risk factor in determining the spread of disease especially new HIV infections, which evidence came from an increase in immigration to Europe associated with variations in distributions of HIV subtypes among cross-border clusters. 23 Migrants were more likely to use substance, because cross-border activities increased access to drugs and drug trafficking due to border stress, environmental risks and psychological factors in border areas. 24 It was nearly 14% using methamphetamine among ethnic minorities of Thailand's border due to easily accessible to illegal drugs.…”
Section: Introductionmentioning
confidence: 99%
“… 21 Population movement was an independent risk factor in determining the spread of disease especially new HIV infections, which evidence came from an increase in immigration to Europe associated with variations in distributions of HIV subtypes among cross-border clusters. 23 …”
Section: Introductionmentioning
confidence: 99%